What is Your Color? A Study of Najdi Bedouin Greetings - Khalid Tag Eldin (Asiatic: IIUM Journal of English Language and Literature, 2023)
This study investigates the greetings of the Bedouin speakers of the Central Najdi Dialect in Afif, Saudi Arabia. It analyzes the greetings used by the subjects and examines the impact of the contextual factors of age, social status, social distance, period of absence, and formality of situation on their choice, and it also identifies the politeness strategies they opted for. The study uses a discourse completion test, interviews, and fieldnotes to collect its data. The study involves 50 subjects randomly chosen from the area. It shows that the subjects use the Islamic greetings, phatic questions, welcoming greetings, temporal greetings, and expressions of longing. It also demonstrates that the subjects use individual and group greetings that are differentiated by the second singular and plural pronoun inflections. Moreover, it shows that the subjects utilise some greetings the reference of which is made to the third singular and plural person pronouns. Also, it reveals that some of the greetings used take the present and past tense markers.